Comparative study on structural properties and combustion kinetics of Chinese Shenhua long flame raw coal and its pyrolytic char. Issue 3 (17th January 2017) - Wang, Yunfei; Song, Yinmin; Zhou, Huacong; Zhi, Keduan; Teng, Yingyue; He, Runxia; Tian, Rongkai; Liu, Quansheng
Abstract : Research on the structural and combustion properties of coal is of great importance for its conversion and applications in view of fundamental studies. In this work, we conducted the first detailed study on the structural properties and combustion kinetics of Chinese Shenhua raw coal (RC) and its pyrolytic char (PC). The combustion kinetics was simulated by using the random pore model (RPM). The results showed that RC and PC were composed of both a plant‐cell‐like structure and a discrete particulate structure. In addition, PC had a larger specific surface area, finer particles, higher aromaticity, and higher degree of aromatic ring condensation than those of RC. Combustion of PC showed higher ignition temperature, lower burnout temperature, and a higher combustion index compared to RC. A high correlation coefficient R 2 (0.999) and a low average error θ (0.008) were obtained using the RPM. The combustion apparent activation energy E and the structural parameter ψ of RC were 40.30 kJ mol −1 and 0.53, respectively. For PC, the values of E and ψ were estimated to be 60.01 kJ mol −1 and 0, respectively. © 2017 American Institute of Chemical Engineers Environ Prog, 36: 766–774, 2017